Eminence of Leader Humility for Follower Creativity During COVID-19: The Role of Self-Efficacy and Proactive Personality - Asghar, Farwa; Mahmood, Shahid; Iqbal Khan, Kanwal; Gohar Qureshi, Madeeha; Fakhri, Mahendra (Frontiers in Psychology, 2022)
The purpose of this study is to understand how leader humility effectively stimulates follower creativity at the workplace during the coronavirus (COVID-19) scenario. Relying on the social cognitive and social information processing theories, this study investigates how leader humility cultivates follower self-efficacy and creativity. Furthermore, it explores the intervening mechanism of follower self-efficacy and examines the moderating role of leader proactive personality. The hypothesized model is empirically tested by collecting data from 405 employees and 87 managers working in the banking sector of Pakistan. The results indicate that leader humility is positively related to follower self-efficacy and follower creativity, which improve the organization's innovation climate and an environment for social sustainability. The follower self-efficacy is also significantly related to follower creativity. The mediation analysis shows that follower self-efficacy mediates the relationship between leader humility and follower creativity. Additionally, leader proactive personality moderates the relation between follower self-efficacy and follower creativity. The study highlights the importance of leader humility for creativity and extends the literature by explaining the role of self-efficacy. Furthermore, the findings may assist the policymakers in how a humble leader heightens employee creativity and social sustainability in COVID-19.